The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1415-790x2012000200002
|View full text |Cite
|
Sign up to set email alerts
|

GSTM1, GSTT1, and GSTP1 polymorphisms, breast cancer risk factors and mammographic density in women submitted to breast cancer screening

Abstract: Genetic polymorphisms in genes related to the metabolism of xenobiotics, such as genes of the glutathione S-transferases (GSTM1, GSTT1, and GSTP1) superfamily have been associated with an increased risk for breast cancer (BC). Considering the high incidence of BC in the city of Porto Alegre in southern Brazil, the purpose of this study was to characterize genotypic and allelic frequencies of polymorphisms in GSTM1, GSTT1, and GSTP1, and correlate these molecular findings with established risk factors for breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…This finding is similar to the Yogyakarta, Indonesian, 10 Khazakstan, 16 Chinese, 7 Taiwanese, 17 Brazilian, 18 and Italian. 19 But in Malay subjects from our http://mji.ui.ac.id data showed a significant deviated from HardyWeinberg equilibrium.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is similar to the Yogyakarta, Indonesian, 10 Khazakstan, 16 Chinese, 7 Taiwanese, 17 Brazilian, 18 and Italian. 19 But in Malay subjects from our http://mji.ui.ac.id data showed a significant deviated from HardyWeinberg equilibrium.…”
Section: Discussionsupporting
confidence: 83%
“…However, to date the results are still somewhat controversial and may vary from population to population. (Gilbert et al, 1993;Silvestrini et al, 1997;Buser et al, 1997;Helzlsouer et al, 1998;Millikan et al, 2000;Mitrunen et al, 2001;Gudmundsdottir et al, 2001;Huang et al, 2003;Egan et al, 2004;Sreenath et al, 2005;Moureau-Zabotto et al, 2006;Unlu et al, 2008;Saxena et al, 2009;Arun et al, 2010;Pongtheerat et al, 2011;Zhang et al, 2011;Ramalhinho et al, 2011;Aguiar et al, 2012;Ramalhinho et al, 2012;Saxena et al, 2013;Khabaz, 2014;Rodríguez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies investigated the possible link between GSTP1 polymorphisms and breast cancer risk, and have shown conflicting results (Gilbert et al, 1993;Silvestrini et al, 1997;Buser et al, 1997;Helzlsouer et al, 1998;Millikan et al, 2000;Mitrunen et al, 2001;Gudmundsdottir et al, 2001;Huang et al, 2003;Egan et al, 2004;Sreenath et al, 2005;Moureau-Zabotto et al, 2006;Unlu et al, 2008;Saxena et al, 2009;Arun et al, 2010;Pongtheerat et al, 2011;Zhang et al, 2011;Ramalhinho et al, 2011;Aguiar et al, 2012;Ramalhinho et al, 2012;Khabaz, 2014;Rodríguez et al, 2014). Many previous studies revealed GSTP1 polymorphism has no correlation with clinical and pathologic tumor characteristics (Buser et al, 1997;Huang et al, 2003) only a few studies showed an inverse correlation with ER (Gilbert et al, 1993;Silvestrini et al, 1997;Moureau-Zabotto et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a lack of expression of the GST mu enzymes that results in decreased antioxidant activity in the cell (Duggan et al, 2013), high accumulation of reactive oxygen species (ROS), and consequently higher susceptibility to carcinogenic events due to DNA damage (McLellan et al, 1997;Wang et al, 2010). It has been suggested that the null GSTM1 is associated with an increased risk of developing some types of cancers including BC (McLellan et al, 1997;de Aguiar et al, 2012;Duggan et al, 2013;Possuelo et al, 2013;Wan et al, 2014). Wan et al (2014), in a meta-analysis study, demonstrated an association of the null GSTM1 genotype with BC in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%